Genetic studies on carcass characteristics of Black Bengal goats - SINGH, L B; SINGH, D K; SINGH, C S P (The Indian Journal of Animal Sciences, 2013)
Data on carcass traits of 51 Black Bengal castrated male kids were analysed to study tim effect of age and weight at slaughter, and weaning weight at 3 months of age. Body weight at slaughter had significant effect on hot-carcass weight, dressing % on empty live weight and proportion of loin with flank. Age at  slaughter had significant effect on dressing % on empty live weight (EL W), proportions of neck and shouldertogether and legs in the carcass. Weaning weight influenced hot. carcass weight, dressing % on EL W and proportion of loin with flank in the carcass. Hot carcass weight, drressing % and muscle increased with  increase in body weight at slaughter. Total bone % in the carcasS declined with the increase in weight at slaughter. Muscle % in the carcass showed increasing trend with the increase in age at slaughter up to 12 months of age. Carcass traits had moderate to high heritability estimates except proportions of breast and brisket, loin with flank and rack. The phenotypic correlations of hot-carcass weight with pre-slaughter traits, viz. body weight, body length, height at withers,   chest-girth and paunch-girth, were positive and significant.Genetic correlations of hot-carcass weight and dressing % with pre-slaughter body weight and linear biometrics were positive and moderate to high in magnitude.